Respostas
respondido por:
1
Encontrar a razão da PA:
r = a2 - a1
r = 32 - 25
r = 7
===
an = a1 + ( n -1 ) . r
a35 = 25 + ( 35 -1 ) . 7
a35 = 25 + 34 . 7
a35 = 25 + 238
a35 = 263
r = a2 - a1
r = 32 - 25
r = 7
===
an = a1 + ( n -1 ) . r
a35 = 25 + ( 35 -1 ) . 7
a35 = 25 + 34 . 7
a35 = 25 + 238
a35 = 263
Camponesa:
Minha primeira verificação, minha homenagem á vc . Obrigada por tudo, por tudo mesmo. <3 <3
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás